2019
DOI: 10.1103/physrevmaterials.3.106001
|View full text |Cite
|
Sign up to set email alerts
|

Electronic phase separation at LaAlO3/SrTiO3 interfaces tunable by oxygen deficiency

Abstract: Electronic phase separation is crucial for the fascinating macroscopic properties of the LaAlO 3 /SrTiO 3 (LAO/STO) paradigm oxide interface, including the coexistence of superconductivity and ferromagnetism. We investigate this phenomenon using angle-resolved photoelectron spectroscopy (ARPES) in the soft-x-ray energy range, where the enhanced probing depth combined with resonant photoexcitation allow us access to fundamental electronic structure characteristics-momentum-resolved spectral function, dispersion… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 55 publications
3
28
0
Order By: Relevance
“…18,19 However, the observed band dispersions and population stayed constant, following the electronic phase separation scenario typical of the STO-based systems. 18,20,42,43 The irradiation-induced increase of the 2DES signal from the high-n s GAO/STO sample was smaller compared to the low-n s one. All reported ARPES data were acquired after an irradiation time of more than 1 hour to insure saturation.…”
Section: Arpes Experimentsmentioning
confidence: 78%
See 1 more Smart Citation
“…18,19 However, the observed band dispersions and population stayed constant, following the electronic phase separation scenario typical of the STO-based systems. 18,20,42,43 The irradiation-induced increase of the 2DES signal from the high-n s GAO/STO sample was smaller compared to the low-n s one. All reported ARPES data were acquired after an irradiation time of more than 1 hour to insure saturation.…”
Section: Arpes Experimentsmentioning
confidence: 78%
“…Firstly, a typical feature of the STO-based systems is the electronic phase separation where conducting regions co-exist with insulating ones. 18,42,43 While experimental FS reflects the local electron density in the conducting areas, the integral n s can be smaller. Secondly, if the interfacial V(r) is sufficiently long-range, it hosts a ladder of quantum-well (QW) states, 44 and the Luttinger count should include the FS sheets through all of them.…”
Section: Depth Extension Of the 2desmentioning
confidence: 99%
“…Another future direction of SW spectroscopic studies on the LAO/STO system is to explore the role of oxygen vacancies. Recently, it is found that the LAO/STO interface electronic structure, which includes the QP (associated with 2DES) and IG states (associated with localized electrons), is tunable through the control of the oxygen vacancies [24,[44][45][46]. SW spectroscopies can show the depth profiles of both the IG and QP states in the oxygen deficient LAO/STO heterostructure, revealing the relationship between oxygen vacancies and 2DES.…”
Section: Discussionmentioning
confidence: 99%
“…[11,73] The complex nature of the heterointerfaces, however, may implicate other defect-scenarios with contributions from both STO and LAO defect sites. Given the reported importance of oxygen vacancies for the properties of LAO/STO interfaces, [35,74,75] it needs to be considered if annihilation and incorporation of oxygen vacancies alone can explain all observed data consistently. For one, however, the reversibility of the appearance of the Ti 3+ signature in the Ti 3d core-level rules out a mere effect of growth-induced excess oxygen vacancies on the STO side of the interface.…”
Section: Doi: 101002/adma202004132mentioning
confidence: 99%